Autonomous-rail Rapid Transit - FENG Jianghua; XIAO Lei; HU Yunqing (Kongzhi Yu Xinxi Jishu)
In order to optimize the structure of urban transportation to meet people’s requirements for fast, punctual, comfortable and convenient public transportation, and to realize the needs of low-cost and high-speed transportation system construction, CRRC Zhuzhou Institute Co., Ltd. launched a new cross-border urban transit system, autonomous-rail rapid transit. This paper comprehensively described the main components of autonomous-rail rapid transit and its principles and key technologies for track-like driving without steel wheels and rails. It systematically introduced ground-based electromechanical systems such as fixed-point charging system, communication signal system, and operation integrated platforms. The technology plan for infrastructure was also described in detail. At present, the system has achieved good results in Zhuzhou, Hunan and Yibin, Sichuan.